Exploring Democracy Beyond the State: Students’ Union Democracy in Chilean Colleges; [Explorando la Democracia Más Allá del Estado: La Democracia en Federaciones Universitarias en Chile] - Disi-Pavlic, R (Universitat Autonoma de Barcelona, 2024)
Political scientists have studied state democracy for decades using sophisticated methods for conceptualization and measurement to evaluate the explanatory power of various theories. They have paid little attention, however, to democracy in nonstate political systems. This paper fills this gap by characterizing democracy in college student government and investigating the factors affecting the levels of students’ union democracy (SUD) in Chilean colleges. Utilizing concepts from political science and sociology, the study identifies different dimensions of SUD with data from 162 campuses in 2018. The dimensions are aggregated to build an index of democracy for students’ unions. Although the majority of Chilean university students attended colleges with democratic unions, our findings reveal a deficit in democratic student representation in most institutions. The article also draws from the comparative politics, trade union democracy, and higher education literatures to explore the factors that vary by institution that could explain differences in levels of SUD. Ordered logistic regression analyses suggest that SUD is associated with institutional quality, membership in inter-university organizations, and student body size and socioeconomic makeup. The results increase our understanding of the features, status, and correlates of democracy beyond the state. © 2024, Universitat Autonoma de Barcelona. All rights reserved.